Mechanisms of co-presence in repetitive drama studio performances - Željka Flegar; Grozdana Lajić Horvat (SCENARIO: Journal for Performative Teaching, Learning, Research, 2024)
When working with older children (ages 9-12) in a drama studio environment (extracurricular theatre and drama education with performative outcomes), keeping everyone present is both an exciting and challenging task. The process towards a performance can encompass several techniques and methods during the creative process, as well as on stage, in three core areas: 1. Impro and Process Drama; 2. Mentoring; 3. Language and Literature. Presence and co-presence occur as a result of focus, accepting, and building which are characteristic of improvisational theatre and process drama techniques that are used to keep students engaged and on task. Students address issues from an autobiographical and collaborative perspective, allowing them to play a part through improvised personal responses. The mentoring is present both outside and inside the play as mentors guide their students, assume some of the roles, and provide a meaningful framework and direction of the play. Fairy tales and well-known literary texts can be used as starting points; they are adapted and transformed on the spot. This results in a creative, spontaneous, and natural use of language that keeps the players present and alert throughout. This paper presents the examples from the Zagreb Youth Theatre (ZKM) Drama Studio's final production "A Bunch of Forest Fairies" (June 2023) which contains elements of Impro, process drama (uncharacteristically performed on stage), inside and outside mentoring (super mentoring), and fairy tale elements that are transformed in a new socio-cultural context. Such an approach enables the players to perform the same play repetitively with the same intensity and presence as the first time, allowing them to re-explore relationships, expressions, and texts in a new and meaningful way.